2000
DOI: 10.1002/(sici)1521-4109(200002)12:3<216::aid-elan216>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A Voltammetric Study of the Complexation of Copper by the Psychoactive Compounds 1,4-Benzodiazepines

Abstract: Complexation of copper ions with the 1,4-benzodiazepines bromazepam, midazolam and chlordiazepoxide is investigated using voltammetric methods, mainly differential pulse polarography in KNO 3 0.10 M and pH 7.0 + 0.1. Additional evidence of the complexation of copper was obtained by an UV-spectrophotometric study. Reduction of the metal ion as well as that of the ligands followed and the voltammetric behavior was interpreted in terms of complex formation. Stability constants have been determined for the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Different methods such as non-aqueous titration [8] flow injection [9], sequential injection [10], voltammetric [4,11], spectrophotometric [12,13], chromatographic [14 -16], capillary electrophoresis [17], and ion selective sensor methods [18] have been reported for the determination of bromazepam in pharmaceutical preparations, blood and plasma. Though BP recommends non-aqueous titration and spectrophotometric methods for the analysis of bromazepam in raw materials [8], there is no official method for its analysis in tablets.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Different methods such as non-aqueous titration [8] flow injection [9], sequential injection [10], voltammetric [4,11], spectrophotometric [12,13], chromatographic [14 -16], capillary electrophoresis [17], and ion selective sensor methods [18] have been reported for the determination of bromazepam in pharmaceutical preparations, blood and plasma. Though BP recommends non-aqueous titration and spectrophotometric methods for the analysis of bromazepam in raw materials [8], there is no official method for its analysis in tablets.…”
Section: Introductionsupporting
confidence: 68%
“…Therefore, most of the stability indicating assay methods have been established using HPLC [25,26]. Therefore, in this study, we developed a simple analytical and stability indicating method for the determination of bromazepam based on bromazepam-copper (II) complex formation using the -N=C-C=N-moiety, that enables bromazepam to form complex with some divalent metal ions such as copper (II), cobalt (II), nickel (II) and iron (II) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The incomplete breakthrough of Cu and the two plateau regions observed may be related to other phenomena rather than adsorption, for instance to precipitation that may occur inside the sepiolite, since pH gradients in the sorbent are generally different from the pH of the bulk phase. In addition, complexation phenomena may probably occur since Cu(II) is known as one of the most effective divalent ions for binding to organic molecules [70,71]. The breakthrough curves obtained for Al and Mg did not present a common sigmoidal shape, neither for the sorption on sepiolite nor for the sorption on the combined system sepiolite/biofilm.…”
Section: Rehabilitation Of Industrial Effluent At Lab-scalementioning
confidence: 95%
“…the analysis of benzodiazepine have been reported including HPLC ion spray mass spectrometry [14,15], tandem mass spectrometry [16,17], polarography [18,19], liquid chromatography [20,21], potentiometry [22,23] and voltammetry [24]. Literature survey revealed that the available complex formation constants were determined in various aqueous-organic solvent systems because many drug compounds and their metal complexes are sparingly soluble in water.…”
mentioning
confidence: 99%